PRE-CERVICAL TORSION OF UTERUS IN A MALABARI DOE - JAYAKUMAR, C; JAYAKUMAR, C; PROMOD, K; DEEPTHl, V (The Indian Journal of Animal Reproduction, 2023)
Pre-cervical torsion of uterus in a Malabari doe, its diagnosis and surgical management is reported.